Application-based guidelines for best practices in plant flow cytometry - Sliwinska, Elwira; Loureiro, João; Leitch, Ilia J; Šmarda, Petr; Bainard, Jillian; Bureš, Petr; Chumová, Zuzana; Horová, Lucie; Koutecký, Petr; Lučanová, Magdalena; Trávníček, Pavel; Galbraith, David W (Cytometry. Part A, 2022)
Flow cytometry (FCM) is currently the most widely-used method to establish nuclear DNA content in plants. Since simple, 1-3-parameter, flow cytometers, which are sufficient for most plant applications, are commercially available at a reasonable price, the number of laboratories equipped with these instruments, and consequently new FCM users, has greatly increased over the last decade. This paper meets an urgent need for comprehensive recommendations for best practices in FCM for different plant science applications. We discuss advantages and limitations of establishing plant ploidy, genome size, DNA base composition, cell cycle activity, and level of endoreduplication. Applications of such measurements in plant systematics, ecology, molecular biology research, reproduction biology, tissue cultures, plant breeding, and seed sciences are described. Advice is included on how to obtain accurate and reliable results, as well as how to manage troubleshooting that may occur during sample preparation, cytometric measurements, and data handling. Each section is followed by best practice recommendations; tips as to what specific information should be provided in FCM papers are also provided.
Keywords: Plants; DNA content; Genome Size; DNA, Plant; intraspecific variation; genome size; in vitro cultures; Genome, Plant; Ploidies; cell cycle; ploidie; Flow Cytometry; délka genomu; DNA rostlinná; DNA base composition; průtoková cytometrie; ploidy; flow cytometric seed screening; genom rostlinný; rostliny; endoreduplication